Effects of ozone therapy on hematological and serum biochemical parameters in dogs affected by visceral leishmaniasis (Research, Society and Development, 2022)
Visceral leishmaniasis (VL) is a zoonosis and chronic disease caused by the protozoan Leishmania spp. which is of great concern to public health. Currently, the drugs used to treat the disease are costly and present undesirable side effects. The use of ozone to treat chronic diseases in both humans and dogs has shown satisfactory results. The aim of this study was to evaluate the ozone therapy in dogs with VL (n=6), administered by intra-abdominal application (IAA), to evaluate hematological and serum biochemical parameters. The protocol involves one gas dose per week for four consecutive weeks. The immunomodulatory action of ozone was determined in the laboratory analyses, confirmed by the increase trend in the white series and maintenance of the renal and hepatic function. Ozone therapy was found to be well tolerated and no adverse effects were observed. Further studies are required to elucidate the mechanisms of action on the infected host.